E-Commerce Pemasaran Hasil Panen Komoditas Pertanian Menerapkan User Centered Design - Citra Yustitya Gobel; Novita Adam (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Based on statistical data, Boalemo Regency is the largest producer of agricultural commodities in Gorontalo Province. Agricultural commodities harvested are rice, coconut, cocoa, palm oil, cloves, corn, sugarcane, coffee, nutmeg, palm sugar, cashew nuts, chili, onion, mango and various other types of fruits and vegetables. However, the lack of information in the agricultural sector is an obstacle to the marketing process of agricultural crops in Boalemo district, where currently the marketing process is still carried out conventionally either through intermediary traders, direct marketing from market to market, and there are also those who use the services of agricultural cooperatives, so that farmers as Producers sometimes only accept market prices which are generally determined by intermediary traders so that the biggest profits are usually obtained by traders. The purpose of this study is to design an e-commerce marketing of agricultural commodities based on a multiuser website with the User Center Design (UCD) method so that it makes it easier for farmer users in the marketing process with a wider and economical marketing area coverage. Website design using PHP programming language and MySQL data storage media. User Centered Design approach where users in every stage of system development are also involved, so that the system formed can be used according to user needs. The results of the discussion of this study produce a user-friendly system because for farmer users there is access to product data management from the input process to the ordering verification process according to the available stock so that this system in Nilia is easy to use during the transaction process for both farmer users as traders and the community as consumers.